Peningkatan Business Value Melalui Implementasi Konsep SMART GOAL pada UMKM “Ngabotram” - Mohamad Hadi Prasetyo (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
MSMEs need an understanding of business values ​​and also need activities to increase these values. Because increasing business value in MSMEs is no less important. This community service (PKM) is carried out with the aim of increasing understanding of business values ​​that can be increased through the SMART GOAL concept in partners, namely MSME Ngabrotram which is engaged in the culinary field. The SMART Goal Setting concept is implemented to make Ngabotram have more value and can increase its business value in the future. This PKM program is in the form of a tiered workshop accompanied by mentoring for the partners concerned which leads to profit, not just turnover. This PKM is one of the efforts to increase the competitiveness of MSME Ngabotram in order to achieve competitive advantage. The problem felt by partners is that there is no and cannot be measured specific goals of the business being run. Finally, they do not understand how goals are set and how to analyze a measurable goal. This greatly affects the business development side which has an impact on its profit. The output targets to be achieved are in the form of publications in community service journals and increasing the understanding and skills of partners as business actors